Tumor necrosis factor receptor modulator spermatogenesis‐associated protein 2 is a novel predictor of outcome in ovarian cancer. Issue 3 (16th February 2019) - Wieser, Verena; Tsibulak, Irina; Degasper, Christine; Welponer, Hannah; Leitner, Katharina; Parson, Walther; Zeimet, Alain G.; Marth, Christian; Fiegl, Heidelinde
Abstract : Inflammation plays a crucial role in the pathogenesis of cancer with tumor necrosis factor‐α (TNF‐α) as a key mediator. Recently, spermatogenesis‐associated protein 2 (SPATA2) was identified as a TNF receptor modulator which is required for TNF‐induced inflammation and apoptosis. The available data on TNF‐α in ovarian cancer (OC) are inconsistent, and SPATA2 is completely uncharacterized in tumorigenesis. We analyzed expression of SPATA2 and TNFA by quantitative real‐time polymerase chain reaction in tissues of 171 patients with low‐grade serous (LGSOC), high‐grade serous (HGSOC), endometrioid and clear cell OC compared with 28 non‐malignant control tissues. We stimulated OC cells (OVCAR3) with pro‐inflammatory (TNF‐α, interleukin [IL]‐1β) and mitogenic stimuli (IL‐6, lysophosphatidic acid) to establish a direct effect between inflammatory signaling and SPATA2 . Pro‐inflammatory, but not mitogenic stimuli, potently induced SPATA2 expression in OC cells. Expression of TNFA and SPATA2 was higher in OC compared with control tissues ( P  =   0.010 and P  =   0.001, respectively) and correlated with each other ( P  =   0.034, r s  = 0.198). When compared with grade 1 cancers, SPATA2 was expressed higher in grade 2 and 3 tumors ( P  =   0.011) as well as in HGSOC compared with LGSOC ( P  =   0.024). Multivariate survival analyses revealed that OC with high SPATA2 expression were associated with reduced progression‐free survival ( P  =   0.048) and overall survival ( P  <   0.001). In conclusion, SPATA2 expression is regulated by TNF‐α and IL‐1β and is found to independently affect clinical outcome in OC patients. These data implicate a role of SPATA2 in tumorigenesis which warrants further investigation in gynecological malignancies. Abstract : TNFA and the TNF receptor modulator SPATA2 are high in ovarian cancer supporting the inflammatory character of this disease. High SPATA2, which was markedly induced by inflammatory stimuli in vitro, independently reflected poor clinical outcome of ovarian cancer patients.